Clinical and molecular findings in a patient with a novel mutation in the deafness-dystonia peptide (DDP1) gene - Binder, Johannes; Hofmann, Sabine; Kreisel, Stefan H.; Wöhrle, Johannes C.; Bäzner, Hansjörg; Krauss, Joachim K.; Hennerici, Michael G.; Bauer, Matthias F. (Brain, 2003)
The Mohr-Tranebjaerg syndrome (MTS) is a rare neurodegenerative disorder characterized by early-onset deafness, dystonia and further neurological abnormalities such as cortical blindness, spasticity, dementia and mental retardation. Causative mutations were identified within the deafness-dystonia peptide (DDP1/TIMM8a) gene on the X-chromosome. The DDP1 protein is located in the intermembrane space of human mitochondria. Here, it acts in a complex together with its partner protein Tim13 in a chaperone-like manner to facilitate the import of nuclear-encoded precursor proteins into the mitochondrial inner membrane. Thus, MTS is a novel type of mitochondrial disorder. To obtain more insight into the pathophysiology of this neurodegenerative disorder, we performed for the first time a comprehensive clinical and functional characterization of a patient suffering from MTS. This patient exhibited a typical combination of deafness, dystonia and visual loss. Sequence analysis of the patient's DDP1 gene revealed a G to C transversion at nucleotide position 38 of the first exon. The mutation affects the ATG start codon, thereby changing methionine to isoleucine (M1I), and leads to a complete absence of the DDP1 protein. In addition, the partner protein Tim13 was found to be significantly reduced, suggesting that Tim13 requires the presence of DDP1 for its stabilization. The assessment of mitochondrial functions showed the enzyme activities of the mitochondrial energy-generating systems to be normal in the muscle biopsy. Structural abnormalities or aggregations of mitochondria were absent. Electron microscopy revealed only a mild neurogenic atrophy. Neurophysiological investigations showed cochlear dysfunction and disturbance of visual pathways. PET and MRI studies revealed a multifocal pattern of neurodegeneration with hypometabolic areas predominantly located over the right striatum and parietal cortex and marked atrophy of the occipital lobes. Although the visual loss is caused predominantly by neurodegeneration of the visual cortex, degeneration of the retina and the optic nerve contributes to the visual impairment. The pathological changes in basal ganglia and sensory cortex demonstrate the disintegration of subcortico-cortical circuits and correlate well with the clinical presentation of multifocal dystonia. The data presented here showed that, in contrast to most of the known mitochondrial disorders, MTS appears not to be associated with a functional defect of the energy generation system of the mitochondria. Whereas the specific mitochondrial dysfunction leading to neuronal loss in MTS remains to be clarified, the electrophysiological and neuroimaging findings allowed the multifocal manifestation of neurodegenerative lesions in MTS to be characterized specifically.